The Effect of Promotion and Brand Image on Product Purchasing Decisions at Liza Bakery - Leonora Puspa; Acep Fatchuroji (ProBisnis : Jurnal Manajemen, 2022)
This study aims to determine the effect of promotion and brand image partially and simultaneously on purchasing decisions for Liza Bakery products. The population in this study were all customers who purchased Liza Bakery products as many as 1201 customers. The sample in this study amounted to 92 respondents with a determination using purposive sampling. The research approach used is a quantitative approach using multiple linear regression analysis with the SPSS version 26 tool. From the results of statistical data analysis, it shows that promotions have a positive and significant effect on purchasing decisions for Liza Bakery products. This can be seen from the results of the t test in which the value of tcount is obtained. 6.768 > ttable 1.986 with a significant level of 0.000 <0.05. The results of statistical data analysis show that brand image has a positive and significant effect on purchasing decisions for Liza Bakery products. This can be seen from the results of the t test in which the value of tcount is 22,560 > ttable 1.986 with a significant level of 0.000 <0.05. This it can be concluded that H_0 is rejected and H_a is accepted. The results of this study indicate that together (simultaneously) the promotion and brand image variables have a positive and significant effect on the purchase decision variable with an Fcount value of 632.839 with a significant level for X1 and X2 to Y of 0.000 and a Ftable value of 3. 10. Thus it can be concluded that H_0 is rejected and H_a is accepted.